Reflective Teaching and Practices in the Classroom - Aryal, Muna (Journal of Multidisciplinary Research Advancements, 2024)
A reflective practice has been warmly influenced in teacher education and development programs on pedagogical practices. A classroom is like a laboratory where a teacher relates teaching theory to teaching practice and observes the students’ responses. This paper attempts to focus on the importance of reflective teaching and check the teachers’ awareness of reflective teaching. It shows the need for reflective practice in classroom practices or how a teacher’s practice in the classroom can be improved through reflective teaching. The information of this study was generated through secondary sources and interviews of research participants, two English teachers of public schools from different parts of Nepal. Also, the study examines how the teacher educator created opportunities for student teachers to develop their reflective practices during their practice teaching sessions.